Implementasi E-Modul Flippingbook pada Materi Teks Eksposisi untuk Meningkatkan Higher Order Thinking Skills Siswa Kelas X SMA - Ramadhani, Irma; Ali, Ali; Kartika, Rika; Soraya, Ratna (Medan Resource Center, 2024)
This study employed the Research and Development (R&D) model to create and evaluate flipping book-assisted E-Module learning products for exposition text material aimed at enhancing Higher Order Thinking Skills (HOTS) in class X at SMA N 19 Medan. The research sought to determine the feasibility and effectiveness of the developed E-Module. The study's population included 400 class X students, with a sample of 39 students from class X-7 selected using purposive sampling. The research followed the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. Data were collected and analyzed quantitatively, then converted into qualitative insights. Validation by material expert I scored 80% (